2020
DOI: 10.1101/2020.06.11.145219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional connectivity within and betweenn-back modulated regions: An adult lifespan PPI investigation

Abstract: Working memory (WM) and its BOLD-related parametric modulation under load decrease with age. Functional connectivity (FC) generally increases with WM load; however, how aging impacts connectivity and whether this is load-dependent, region-dependent, or associated with cognitive performance is unclear. This study examines these questions in 170 healthy adults (Mage = 52.99  19.18) who completed fMRI scanning during an n-back task (0-, 2-, 3-, and 4back). FC was estimated utilizing a modified generalized psycho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…2012 ) to investigate the task-related modulation of functional connectivity, for semantic fluency. Furthermore, we applied a modified version of gPPI methods to examine the functional connections between individual ROIs during the semantic fluency task ( Pongpipat et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…2012 ) to investigate the task-related modulation of functional connectivity, for semantic fluency. Furthermore, we applied a modified version of gPPI methods to examine the functional connections between individual ROIs during the semantic fluency task ( Pongpipat et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, results are more inconsistent for task-related changes in functional connectivity with age. Across a range of cognitive tasks, studies reported a similar pattern as for resting state investigations (Geerligs et al, 2014;Spreng et al, 2016), no changes for within-but only for between-network connectivity (Gallen et al, 2016;Grady et al, 2016), as well as age invariance (Pongpipat et al, 2020;Trelle et al, 2019). In the domain of semantic cognition, findings are sparse with one study observing reduced within-network integration for a semantic fluency task which was not associated with a poorer performance in older adults (Marsolais et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
“…We conducted psychophysiological interaction (PPI) analyses using the gPPI toolbox for SPM12 (McLaren et al, 2012) to investigate task-related modulation of functional connectivity associated with the semantic fluency and the counting task. Furthermore, we applied a modified version of gPPI methods to examine functional connections between individual ROIs during the semantic fluency task (Pongpipat et al, 2020). Seed regions were defined for all previously identified global maxima that were located within the MDN and the DMN (Table 2).…”
Section: Methodsmentioning
confidence: 99%